Radiofrequency ablation via an implanted self-expandable metallic stent to treat in-stent restenosis in a rat gastric outlet obstruction model - Won, Dong-Sung; Park, Yubeen; Zeng, Chu Hui; Ryu, Dae Sung; Kim, Ji Won; Kang, Jeon Min; Kim, Song Hee; Kim, Hyung-Sik; Lee, Sang Soo; Park, Jung-Hoon (Frontiers in Bioengineering and Biotechnology, 2023)
Background: In-stent restenosis caused by tissue hyperplasia and tumor growth through the wire meshes of an implanted self-expandable metallic stent (SEMS) remains an unresolved obstacle. This study aimed to investigate the safety and efficacy of SEMS-mediated radiofrequency ablation (RFA) for treating stent-induced tissue hyperplasia in a rat gastric outlet obstruction (GOO) model.The ablation zone was investigated using extracted porcine liver according to ablation time. The optimal RFA parameters were evaluated in the dissected rat gastric outlet.We allocated 40 male rats to four groups of 10 rats as follows: group A, SEMS placement only; group B, SEMS-mediated RFA at 4-weeks; group C, SEMS-mediated RFA at 4-weeks and housed until 8-weeks; and group D, SEMS-mediated RFA at 4-and 8-weeks. Endoscopy and fluoroscopy for in-vivo imaging and histological and immunohistochemical analysis were performed to compare experimental groups.Results: Stent placement and SEMS-mediated RFA with optimized RFA parameter were technically successful in all groups. Granulation tissue formation-related variables were significantly higher in group A than in groups B-D (all p < 0.05). Endoscopic and histological findings confirmed the degrees of stent-induced tissue hyperplasia in group D was significantly lower than groups B and C (all p < 0.05). HSP 70 and TUNEL expression was significantly higher in groups B-D than in group A (all p < 0.001).The implanted SEMS-mediated RFA successfully managed stent-induced tissue hyperplasia and repeated or periodic RFA seems to be more effective to treat in-stent restenosis in a rat GOO model.